Genetics and biology of asthma 2010: La' ci darem la mano - Vercelli, Donata (Journal of allergy and clinical immunology, 2010)
[...]Debbie Meyers, Gene Bleecker, and their collaborators performed a GWAS on a population of patients with severe or difficult-to-treat asthma to identify genes that are involved in asthma pathogenesis.4 In this study 292,443 SNPs were tested for association with asthma in 473 cases from The Epidemiology and Natural History of Asthma: Outcomes and Treatment Regimens (TENOR) population and 1,892 Illumina general population control subjects. [...]as we recently discussed elsewhere,21 it is difficult to assess how much environmental exposures affect the outcome of GWASs, but it is reasonable to surmise that environmental heterogeneities might contribute significantly to discrepancies in GWAS results.